Analysis the Effect of Mergers and Acquisıtions on Firm Performance and Earning Quality in Firms Listed on the IDX - Miranda Irawan; Edi Edi (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
This study determine whether the firm performance and earning quality has changed after mergers and acquisitions. Firms that conducted mergers and acquisitions between 2010-2014 and were listed on the IDX were the objects of this research. The results showed that after mergers and acquisitions, the firm's overall profitability, liquidity and solvency decreased significantly. However, this decline was also accompanied by an increase in earning quality, although not so significant. These research findings provide a new insight that after mergers and acquisitions, the firm focus on improving earnings quality first, thus sacrificing other financial performance such as profitability, liquidity and solvency